M5 Comparison of respiratory health-related quality of life in patients with intractable breathlessness due to advanced cancer or advanced COPD. (12th November 2015) - Javadzadeh, S; Chowienczyk, S; Booth, S; Farquhar, M
Abstract : Introduction and objectives: Breathlessness is common in patients with advanced cancer and almost universal in advanced chronic obstructive pulmonary disease (COPD), but studies suggest their experiences of breathlessness vary. Our objective was to seek quantitative evidence of differences in respiratory health-related quality of life (HRQoL) between these groups using the Chronic Respiratory Questionnaire (CRQ) and to contribute to the debate on the validity of CRQ in patients with cancer. Methods: The CRQ-Original was completed within baseline interviews for a randomised control trial of a palliative intervention for breathlessness. Independent-Samples Mann-Whitney U Tests were performed to identify significant differences in median scores for the four CRQ domains (mastery, dyspnoea, emotional function, fatigue) in patients with advanced COPD (n = 73) or advanced cancer (n = 67.) The Minimally Clinically Important Difference (MCID) of 0.5 was applied to determine clinical significance. Results: Patients with advanced COPD scored lower across all four CRQ domains. This was statistically significant for the dyspnoea, mastery, and emotional functioning scores (p < 0.05), and clinically significant for latter two, suggesting poorer respiratory HRQoL (Table 1). Conclusions: Patients with breathlessness due to advanced COPD had worse respiratory HRQoL than those due to advanced cancer. There are three potential explanations for this finding: (1) there may be a greater burden of breathlessness in COPD due to condition-longevity, (2) the burden of breathlessness may be less in cancer due to the episodic nature of the symptom in malignant conditions, and (3) it may reflect variance in palliative referral thresholds by disease group. Our results further suggest that greater access to palliative care is needed in advanced COPD and that formal psychometric testing of the CRQ may be warranted in cancer.